Смотри..........................
Х= - 1
Х1=(3+корень5)/2
Х2=(3-корень5)/2
Объяснение:
Х^3-2х^2-2х+1=0
(Х^3+1)-(2х^2+2х)=0
(x+1)(x^2-x+1)-2x(x+1)=0
(x+1)(x^2-x+1-2x)=0
(x+1)(x^2-3x+1)=0
x+1=0 и x^2-3x+1=0
x= - 1 D=b^2 - 4ac=9-4×1×1=5
X1=(3+корень5)/2
Х2=(3-корень5) /2
Смотри..........................
Х= - 1
Х1=(3+корень5)/2
Х2=(3-корень5)/2
Объяснение:
Х^3-2х^2-2х+1=0
(Х^3+1)-(2х^2+2х)=0
(x+1)(x^2-x+1)-2x(x+1)=0
(x+1)(x^2-x+1-2x)=0
(x+1)(x^2-3x+1)=0
x+1=0 и x^2-3x+1=0
x= - 1 D=b^2 - 4ac=9-4×1×1=5
X1=(3+корень5)/2
Х2=(3-корень5) /2